MAMPUKAH DIVERSIFIKASI ASET MENINGKATKAN NILAI PASAR BANK? - DYAH NIRMALAWATI TAURUSIANINGSIH (Al-Masraf: Jurnal Lembaga Keuangan dan Perbankan, 2018)
The theme of the research is "Banks and Financial Institutions".This research was conducted to analyse the impact of asset diversification on bank to its market value. By using 11 banks which are categorized as banks that have core capital more than 500 trillion Rupiah and also listed on Indonesia Stock Exchange (IDX) since 2004 as a research sample, we found that conglomerate discount was exist on bank that having a small asset only. Otherwise, the more diversified bank, the higher its market value.